2012
DOI: 10.1210/en.2012-1335
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Deletion of Trp53 Compromises Antioxidant Responses in the Mouse Decidua

Abstract: Preterm birth is a global health issue impacting millions of mothers and babies. However, the etiology of preterm birth is not clearly understood. Our recent finding that premature decidual senescence with terminal differentiation is a cause of preterm birth in mice with uterine Trp53 deletion, encoding p53 protein, led us to explore other potential factors that are related to preterm birth. Using proteomics approaches, here, we show that 183 candidate proteins show significant changes in deciduae with Trp53 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 49 publications
0
40
0
Order By: Relevance
“…TRP53 polymorphisms have also been associated with aging and lifespan in humans (36,54). Our recent proteomics study showed that deciduae in Trp53 loxP/loxP Pgr Cre/+ females manifest an increased signature for oxidative stress, with downregulation of many antioxidant enzymes, including PRDX6 (24). PRDX6 plays a role during pregnancy in mice with deletion of Fkbp52, an immunophilin co-chaperone for nuclear PR, which show reduced uterine P 4 responsiveness (55-57).…”
Section: Figurementioning
confidence: 99%
“…TRP53 polymorphisms have also been associated with aging and lifespan in humans (36,54). Our recent proteomics study showed that deciduae in Trp53 loxP/loxP Pgr Cre/+ females manifest an increased signature for oxidative stress, with downregulation of many antioxidant enzymes, including PRDX6 (24). PRDX6 plays a role during pregnancy in mice with deletion of Fkbp52, an immunophilin co-chaperone for nuclear PR, which show reduced uterine P 4 responsiveness (55-57).…”
Section: Figurementioning
confidence: 99%
“…In mice, persistently high levels of senescent cells in uteri by tissue-specific deletion of the tumor protein p53 (Trp53) gene in progesterone receptor-expressing cells also reduced decidual growth without altering the number of implantation sites (Hirota et al 2010). Further proteomic analysis on these mice showed downregulated expression of a cluster of antioxidant enzymes in Trp53-deficient decidua (Burnum et al 2012), implicating the involvement of oxidative stress with increased presence of senescent cells in the uterus. Moreover, these tissue-specific Trp53-deficient mice have increased the incidence of preterm birth and neonatal deaths, partly due to the activation of a prostaglandinmediated pathway (Hirota et al 2010).…”
Section: Cellular Senescence and Uterine Agingmentioning
confidence: 99%
“…Identification and quantification of the detected peptide peaks were performed using the AMT tag approach (17,27,28). Both Q Exactive and IMS-MS analyses were utilized to populate the database with LC elution times, IMS drift times and accurate mass information for each peptide tag ( Fig.…”
Section: Experimental Design and Statistical Rational: Lc-ms And Lc-imentioning
confidence: 99%
“…Peptides observed in each instrument were compared, and only those agreeing with high mass accuracy (within 2 ppm) and LC elution time (Ͻ0.5%) were populated with IMS drift times in the PDX tumor database used in this work (28). The LC-MS and LC-IMS-MS raw data were processed using in-house developed informatics tools (publicly available at https://omics.pnl.gov/software) with algorithms for peak-picking and determining isotopic distributions and charge states for feature definition (30).…”
Section: Experimental Design and Statistical Rational: Lc-ms And Lc-imentioning
confidence: 99%
See 1 more Smart Citation